Advanced materials for enamel remineralization - Xu, Jiarong; Shi, Hui; Luo, Jun; Yao, Haiyan; Wang, Pei; Li, Zhihua; Wei, Junchao (Frontiers in Bioengineering and Biotechnology, 2022)
Enamel caries is a chronic irreversible disease caused by cariogenic bacteria. General restorative treatment is cleaning the cavity and then fill it with functional materials such as bioglass or resin. Besides, remineralization treatment is also an important means of caries prevention and treatment. Enamel remineralization requires reconstruction of the structure and restoration of the hardness under the guidance of functional materials. Therefore, remineralization materials have great potential for clinical application. In this review, these advanced materials for enamel remineralization were briefly summarized, furthermore, an outlook on the perspective of remineralization materials were addressed.